2021
DOI: 10.3390/ijms22084119
|View full text |Cite
|
Sign up to set email alerts
|

Towards Novel Treatments for Schizophrenia: Molecular and Behavioural Signatures of the Psychotropic Agent SEP-363856

Abstract: Schizophrenia is a complex psychopathology whose treatment is still challenging. Given the limitations of existing antipsychotics, there is urgent need for novel drugs with fewer side effects. SEP-363856 (SEP-856) is a novel psychotropic agent currently under phase III clinical investigation for schizophrenia treatment. In this study, we investigated the ability of an acute oral SEP-856 administration to modulate the functional activity of specific brain regions at basal levels and under glutamatergic or dopam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…While TAAR1 partial and full agonists can differentially modulate baseline DA neuron firing, consistent antipsychotic-like effects of both partial and full agonists have been reported in several rodent models of schizophrenia (Table 2). TAAR1 agonists robustly block hyperactivity induced by cocaine, amphetamine, PCP and L-687,414 in rodents [74,86,106,111,112,122], likely through direct effects on DA neurotransmission and/or upstream modulation of glutamatergic activity. Thus, various TAAR1 agonist profiles are effective in paradigms based on hyperdopaminergic activity (i.e., cocaine, amphetamine) and NMDA receptor hypofunction (PCP, L-687,414), similar to antipsychotics.…”
Section: Role Of Taar1 In Psychosis and Dopaminergic Tonementioning
confidence: 98%
“…While TAAR1 partial and full agonists can differentially modulate baseline DA neuron firing, consistent antipsychotic-like effects of both partial and full agonists have been reported in several rodent models of schizophrenia (Table 2). TAAR1 agonists robustly block hyperactivity induced by cocaine, amphetamine, PCP and L-687,414 in rodents [74,86,106,111,112,122], likely through direct effects on DA neurotransmission and/or upstream modulation of glutamatergic activity. Thus, various TAAR1 agonist profiles are effective in paradigms based on hyperdopaminergic activity (i.e., cocaine, amphetamine) and NMDA receptor hypofunction (PCP, L-687,414), similar to antipsychotics.…”
Section: Role Of Taar1 In Psychosis and Dopaminergic Tonementioning
confidence: 98%
“… 2 , 3 Nonclinical studies support agonism at TAAR1 and 5-HT1A receptors as contributing to the mechanism of action. 4 In vivo , ulotaront has demonstrated broad efficacy in nonclinical models of schizophrenia, including phencyclidine (PCP)-induced hyperactivity, 4 , 5 prepulse inhibition (PPI) of the acoustic startle response, 4 and subchronic PCP-induced deficits in social interaction. 4 , 5 It also significantly reduced ketamine-induced increases in striatal dopamine synthesis capacity, 6 and it demonstrated inhibitory effects in ventral tegmental area (VTA) neurons in slice and in vivo electrophysiology studies, 4 likely mediated via action of TAAR1.…”
mentioning
confidence: 99%
“…Among the numerous compounds currently under investigation, the development of the selective GlyT1 inhibitor BI 425809 [97][98][99] and the TAAR1 agonist ulotaront (SEP-363856) [288][289][290][291] is the most advanced. The breakthrough therapy designation granted for both substances by the FDA enables regulatory monitoring of the approval process.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the 26-week open-label extension study [ 289 ] revealed a continuous reduction in the PANSS total score and in the Clinical Global Impression-Severity score, with a relatively high completion rate and absence of extrapyramidal-related adverse effects. While neither publication specifically addresses the effects of SEP-363856 on CIAS, preclinical studies indicate a benefitial effect of the substance on cognitive deficits in a psychosis animal model [ 290 ]. Ulotaront was granted a breakthrough therapy designation by the FDA for the treatment of patients with schizophrenia in May 2019 [ 291 , 286 ].…”
Section: Modulation Of the Taar1mentioning
confidence: 99%